Validation of PANS and active flow control for a generic truck cabin. Issue 171 (December 2017) - Minelli, G.; Hartono, E. Adi; Chernoray, V.; Hjelm, L.; Basara, B.; Krajnović, S.
Abstract: This paper presents a drag reduction study using active flow control (AFC) on a generic bluff body. The model consists of a simplified truck cabin, characterized by sharp edge separation on top and bottom edges and pressure induced separation on the two other rounded vertical front corners. The pressure induced separation reproduces the flow detachment occurring at the front A-pillar of a real truck (Schuetz, 2015). The prediction of the flow field by partially averaged Navier-Stokes (PANS) simulations, conducted on a relatively coarse mesh, is validated against wind tunnel data (pressure measurements and particle image velocimetry (PIV)) and resolved large eddy simulations (LES) data. The Reynolds number for both simulations and experiments is R e = 5 × 10 5 (which corresponds to 1/6 of a full scale truck R e ) based on the inlet velocity U i n f and the width of the model W = 0.4 m. A validation of PANS results is followed by a CFD study on the actuation frequency that minimizes the aerodynamic drag and suppresses the side recirculation bubbles. PANS accurately predicts the flow field measured in experiments and predicted by a resolved LES. The side recirculation bubble of a simplified truck cabin model is suppressed almost completely and a notable drag reduction by means of AFC is observed.